Egypt land of ancient wonders - Slodwoski, Andrew; Haley, Graham (London : International Video Network, 1993)
Visit Cairo, a centuries-old city, where sleek offices tower near ancient alleyways, bustling bazaars and hundreds of mosques including the splendid Alabaster Mosque. Travel along the Nile, Egypt's lifeblood, to the monumental pyramids of Giza and the Mighty Sphinx.
Copy available in DVD format
Keywords: Egypt -- Description and travel; Egypt -- Social life and customs